JILBAB DALAM PANDANGAN ULAMA KLASIK DAN KONTEMPORER (Kajian Filosofis dan Implementatif) - Nur Asia Hamzah; Zaenal Abidin (Universitas Islam Negeri Alauddin, 2021)
This article aims to examine the hijab in Islam philosophically and implementationally. Through a search for literature sources and content analysis, this article finds that the essence of the hijab is all clothing that covers all members of a woman's body. By the majority of scholars, they do not exclude the face and palms. The law of hijab according to the views of classical scholars, there are differences regarding the limits of the aurat that must be covered, but they agree that the obligation to veil for Muslim women is a provision from Allah that must be obeyed. According to them, hijab is not only Arab culture, therefore the shari'ah of hijab is generally accepted by all Muslim women in the world. That is different from the views of contemporary scholars, the hijab is not a mandatory law that must be implemented. The verse about hijab only talks about local Arab culture. Thus, the standard of women's clothing is based on a measure of respectability and modesty in a particular region. The implementation of the hijab law depends on the goal of maintaining the honor and glory of Muslim women, free from distractions and temptations from fasiq people, more easily recognizable. As for the conditions, among others: it must cover the entire body except what is commonly seen, must be thick, must be loose, and must not resemble men's clothing.Keywords: Hijab in Islam; philosophically; implementationally; classical scholars; contemporary scholars.Â AbstrakArtikel ini betujuan untuk mengkaji jilbab dalam Islam secara filosofis dan implementatif. Melalui penelusuran sumber primer dan sekunder, artikel ini menemukan bahwa hakikat jilbab adalah setiap pakaian yang menutupi seluruh anggota badan perempuan, oleh mayoritas ulama, mereka mengecualikan muka dan telapak tangan. Hukum jilbab menurut pandangan ulama klasik terdapat perbedaan terkait batasan aurat yang harus ditutupi, namun mereka sepakat bahwa kewajiban berjilbab bagi wanita muslimah adalah syariat dari Sya>riâ€˜ yang harus ditaati. Jilbab tidak hanya sekedar budaya orang Arab, karena itu yariâ€™at jilbab berlaku umum bagi seluruh wanita muslimah di dunia. Berbeda halnya dengan ulama kontemporer, jilbab bukanlah sebuah syariat wajib yang harus dilaksanakan. Ayat tentang jilbab hanya berbicara tentang budaya lokal Arab. Dengan demikian, Standar pakaian wanita didasarkan pada ukuran kehormatan dan kesopanan di daerah tertentu. Implementasi hukum pemakaian jilbab terpulang kepada tujuannya untuk menjaga kehormatan dan kemuliaan wanita muslimah, bebas dari gangguan maupun godaan orang-orang fasiq, lebih mudah dikenali. Adapun syaratnya, antara lain: harus menutupi seluruh tubuh kecuali yang biasa tampak, harus tebal, harus longgar, dan tidak boleh menyerupai pakaian laki-laki.ØªÙ‡Ø¯Ù Ù‡Ø°Ù‡ Ø§Ù„Ù…Ù‚Ø§Ù„Ø© Ø¥Ù„Ù‰ Ø¯Ø±Ø§Ø³Ø© Ø§Ù„ØØ¬Ø§Ø¨ ÙÙŠ Ø§Ù„Ø¥Ø³Ù„Ø§Ù… ÙÙ„Ø³ÙÙŠØ§Ù‹ ÙˆØªØ·Ø¨ÙŠÙ‚ÙŠØ§Ù‹. Ù…Ù† Ø®Ù„Ø§Ù„ Ø§Ù„Ø¨ØØ« Ø¹Ù† Ù…ØµØ§Ø¯Ø± Ø§Ù„Ù…ÙƒØªØ¨Ø© Ù…Ø¹ ØªØÙ„ÙŠÙ„ Ø§Ù„Ù…ØØªÙˆÙ‰ØŒ ØªØ¬Ø¯ Ù‡Ø°Ù‡ Ø§Ù„Ù…Ù‚Ø§Ù„Ø© Ø£Ù† Ø§Ù„ØØ¬Ø§Ø¨ Ù‡Ùˆ ÙƒÙ„ Ø§Ù„Ù…Ù„Ø§Ø¨Ø³ Ø§Ù„ØªÙŠ ØªØºØ·ÙŠ Ø¬Ù…ÙŠØ¹ Ø£Ø¹Ø¶Ø§Ø¡ Ø¬Ø³Ø¯ Ø§Ù„Ù…Ø±Ø£Ø©. ÙˆÙ„Ø¬Ù…Ù‡ÙˆØ± Ø§Ù„Ø¹Ù„Ù…Ø§Ø¡ Ù„Ø§ ÙŠØªÙˆÙ‚Ø¹ÙˆÙ† Ø§Ù„ÙˆØ¬Ù‡ ÙˆØ§Ù„ÙƒÙÙŠÙ†. ÙˆØ´Ø±ÙŠØ¹Ø© Ø§Ù„ØØ¬Ø§Ø¨ ÙÙŠ Ø±Ø£ÙŠ Ø§Ù„Ø¹Ù„Ù…Ø§Ø¡ Ø§Ù„ÙƒÙ„Ø§Ø³ÙŠÙƒÙŠÙŠÙ†ØŒ Ù‡Ù†Ø§Ùƒ Ø§Ø®ØªÙ„Ø§ÙØ§Øª ÙÙŠ ØØ¯ÙˆØ¯ Ø§Ù„Ø¹ÙˆØ±Ø§Øª Ø§Ù„ØªÙŠ ÙŠØ¬Ø¨ ØªØºØ·ÙŠØªÙ‡Ø§ØŒ Ù„ÙƒÙ†Ù‡Ù… Ø§ØªÙÙ‚ÙˆØ§ Ø¹Ù„Ù‰ Ø£Ù† ÙˆØ¬ÙˆØ¨ Ø§Ù„ØØ¬Ø§Ø¨ Ù„Ù„Ù…Ø±Ø£Ø© Ø§Ù„Ù…Ø³Ù„Ù…Ø© ØÙÙƒÙ… Ù…Ù† Ø¹Ù†Ø¯ Ø§Ù„Ù„Ù‡ Ø§Ù„Ø°Ù‰ ÙŠØ¬Ø¨ Ø·Ø§Ø¹ØªÙ‡. ÙˆÙÙ‚Ø§ Ù„Ù‡Ù…ØŒ Ø§Ù„ØØ¬Ø§Ø¨ Ù„ÙŠØ³ Ù…Ø¬Ø±Ø¯ Ø«Ù‚Ø§ÙØ© Ø¹Ø±Ø¨ÙŠØ©ØŒ Ù„Ø°Ù„Ùƒ ÙØ¥Ù† Ø´Ø±ÙŠØ¹Ø© Ø§Ù„ØØ¬Ø§Ø¨ Ù…Ù‚Ø¨ÙˆÙ„Ø© Ø¨Ø´ÙƒÙ„ Ø¹Ø§Ù… Ù…Ù† Ù‚Ø¨Ù„ Ø¬Ù…ÙŠØ¹ Ø§Ù„Ù†Ø³Ø§Ø¡ Ø§Ù„Ù…Ø³Ù„Ù…Ø§Øª ÙÙŠ Ø§Ù„Ø¹Ø§Ù„Ù…. ÙˆÙ‡Ø°Ø§ ÙŠØ®ØªÙ„Ù Ø¹Ù† Ø¢Ø±Ø§Ø¡ Ø§Ù„Ø¹Ù„Ù…Ø§Ø¡ Ø§Ù„Ù…Ø¹Ø§ØµØ±ÙŠÙ†ØŒ ÙØ§Ù„ØØ¬Ø§Ø¨ Ø¹Ù†Ø¯Ù‡Ù…ØŒ Ù„ÙŠØ³ Ù‚Ø§Ù†ÙˆÙ†Ù‹Ø§ Ø¥Ù„Ø²Ø§Ù…ÙŠÙ‹Ø§ ÙŠØ¬Ø¨ ØªÙ†ÙÙŠØ°Ù‡. Ø§Ù„Ø¢ÙŠØ© Ø§Ù„ÙƒØ±ÙŠÙ…Ø© Ø§Ù„ØªÙŠ ØªØªØØ¯Ø« Ø¹Ù† Ø§Ù„ØØ¬Ø§Ø¨ ØªØªØØ¯Ø« ÙÙ‚Ø· Ø¹Ù† Ø§Ù„Ø«Ù‚Ø§ÙØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø§Ù„Ù…ØÙ„ÙŠØ©. ÙˆØ¨Ø§Ù„ØªØ§Ù„ÙŠØŒ ÙØ¥Ù† Ù…Ø¹ÙŠØ§Ø± Ù…Ù„Ø§Ø¨Ø³ Ø§Ù„Ù†Ø³Ø§Ø¡ ÙŠÙ‚ÙˆÙ… Ø¹Ù„Ù‰ Ù‚Ø¯Ø± Ù…Ù† Ø§Ù„Ø§ØØªØ±Ø§Ù… ÙˆØ§Ù„ØªÙˆØ§Ø¶Ø¹ ÙÙŠ Ù…Ù†Ø·Ù‚Ø© Ù…Ø¹ÙŠÙ†Ø©. ÙŠØ¹ØªÙ…Ø¯ ØªØ·Ø¨ÙŠÙ‚ Ù‚Ø§Ù†ÙˆÙ† Ø§Ø±ØªØ¯Ø§Ø¡ Ø§Ù„ØØ¬Ø§Ø¨ Ø¹Ù„Ù‰ Ø§Ù„Ù‡Ø¯Ù Ø§Ù„Ù…ØªÙ…Ø«Ù„ ÙÙŠ Ø§Ù„ØÙØ§Ø¸ Ø¹Ù„Ù‰ Ø´Ø±Ù ÙˆÙ…Ø¬Ø¯ Ø§Ù„Ù…Ø±Ø£Ø© Ø§Ù„Ù…Ø³Ù„Ù…Ø©ØŒ Ø®Ø§Ù„ÙŠØ© Ù…Ù† Ø§Ù„Ø§Ù†ØØ±Ø§ÙØ§Øª ÙˆØ§Ù„Ø¥ØºØ±Ø§Ø¡Ø§Øª Ù…Ù† Ù‚Ø¨Ù„ Ø§Ù„ÙØ§Ø³Ù‚ØŒ ÙˆÙŠØ³Ù‡Ù„ Ø§Ù„ØªØ¹Ø±Ù Ø¹Ù„ÙŠÙ‡Ø§. Ø£Ù…Ø§ Ù…Ù† Ø¨ÙŠÙ† Ø§Ù„Ø´Ø±ÙˆØ·Ø› ÙŠØ¬Ø¨ Ø¹Ù„Ù‰ Ø§Ù„Ù†Ø³Ø§Ø¡ ØªØºØ·ÙŠØ© Ø§Ù„Ø¬Ø³Ù… Ø¨Ø§Ù„ÙƒØ§Ù…Ù„ Ø¨Ø§Ø³ØªØ«Ù†Ø§Ø¡ Ù…Ø§ Ù‡Ùˆ Ø¸Ø§Ù‡Ø± Ø¹Ø§Ø¯Ø©ØŒ ÙˆÙŠØ¬Ø¨ Ø£Ù† ØªÙƒÙˆÙ† Ø§Ù„Ù…Ù„Ø§Ø¨Ø³ Ø³Ù…ÙŠÙƒØ© (ØºÙŠØ± Ø´ÙØ§ÙØ©) ØŒ ÙˆÙŠØ¬Ø¨ Ø£Ù† ØªÙƒÙˆÙ† ÙˆØ§Ø³Ø¹Ø© (ØºÙŠØ± Ø¶ÙŠÙ‚Ø©) ØŒ ÙˆÙŠØ¬Ø¨ Ø£Ù„Ø§ ØªØ´Ø¨Ù‡ Ù…Ù„Ø§Ø¨Ø³ Ø§Ù„Ø±Ø¬Ø§Ù„.